A finite element unified formulation for composite laminates in bending considering progressive damage. (March 2022) - Ferreira, Gregório F.O.; Almeida, José Humberto S.; Ribeiro, Marcelo L.; Ferreira, António J.M.; Tita, Volnei
Abstract: This works proposes a novel approach to develop higher-order finite elements by taking progressive damage into account in the formulation. The approach is based on Carrera's unified formulation (CUF) while the damage model is based on continuum damage mechanics (CDM) principles, which is implemented as a UEL (User Element subroutine) written in FORTRAN and linked to Abaqus. The approach is assessed by simulating a plate under distributed and sinusoidal loads. Besides, a progressive damage analysis of a composite coupon under three-point bending is simulated, and the numerical predictions are compared against experimental results, showing good correlation. The main findings show that the implemented UEL is accurate and fast enough to predict progressive failure events and the in-plane damage mechanisms for composite laminates under bending loadings. Highlights: A damage model with finite elements based on CUF is developed. The integrated framework is implements as a single UEL subroutine. All steps to develop the subroutine are explained in detail. Results are validated against experimental findings.